2002
DOI: 10.1095/biolreprod.102.003558
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Genes and P-Glycoprotein in the Testis of the Rat, Mouse, Guinea Pig, and Human1

Abstract: Study of the multidrug resistance phenomenon in tumor cell lines has led to the discovery of the product of the multidrug resistance (MDR) type 1 genes, the plasma membrane P-glycoprotein (P-gp) that functions as an energy-dependent pump for the efflux of diverse anticancer drugs. P-gp was also recently identified in normal epithelial cells with secretory/excretory functions and in the endothelial cells of the capillary blood vessels in the brain and the testis. These endothelial cells are key elements of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
84
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 49 publications
4
84
2
1
Order By: Relevance
“…In addition, its efflux was completely suppressed by verapamil, an inhibitor of Pgp that inhibits the efflux of rhodamine 6G in a competitive manner [23,24]. Our findings are very similar to those of a recent report using the testes of several species [14]. High expression of Pgp in the ovaries, testes, adrenal glands, and reproductive organs suggests a function closely associated with steroid hormone transport.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, its efflux was completely suppressed by verapamil, an inhibitor of Pgp that inhibits the efflux of rhodamine 6G in a competitive manner [23,24]. Our findings are very similar to those of a recent report using the testes of several species [14]. High expression of Pgp in the ovaries, testes, adrenal glands, and reproductive organs suggests a function closely associated with steroid hormone transport.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, its efflux was completely suppressed by verapamil, an inhibitor of Pgp that inhibits the efflux of rhodamine 6G in a competitive manner [23,24]. Our findings are very similar to those of a recent report using the testes of several species [14]. …”
supporting
confidence: 91%
See 2 more Smart Citations
“…20,21,48 Unlike P-glycoprotein, which is localized to the BTB and expressed by Sertoli cells, Leydig cells and late spermatids, 20,50,51 and Mrp1, which is also localized to Sertoli cells at the BTB in humans and mice, 20,52 , but not in endothelial cells in the microvessels of rat testes, 53 Bcrp is not found at the BTB in rat testes. 20,21,33 Recent studies have shown that Bcrp is also expressed by Sertoli cells and late spermatids (steps 17-18, but not step 19) in rat testes in a tightly stage-specific pattern at the Sertoli/spermatid interface at the apical ES, in stage VI-VIII tubules (Figure 3).…”
Section: Bcrp and Spermatogenesis Xj Qian Et Al 457mentioning
confidence: 99%